Carpal bones of Nacholapithecus kerioi, a Middle Miocene Hominoid From Northern Kenya. Issue 3 (22nd March 2016) - Ogihara, Naomichi; Almécija, Sergio; Nakatsukasa, Masato; Nakano, Yoshihiko; Kikuchi, Yasuhiro; Kunimatsu, Yutaka; Makishima, Haruyuki; Shimizu, Daisuke; Takano, Tomo; Tsujikawa, Hiroshi; Kagaya, Miyuki; Ishida, Hidemi
ABSTRACT: Objectives: The carpal bones of the middle Miocene hominoid Nacholapithecus kerioi are described based on new materials. Materials and Methods: The materials comprise a trapezoid, three capitates, two hamates, a centrale, a lunate, a triquetrum, and a pisiform, collected during the 2001 and 2002 field seasons from Nachola, Kenya. We also describe a pisiform recently assigned to the type specimen of N. kerioi, KNM‐BG 35250. Results: In the Nacholapithecus wrist, the ulnar styloid process articulates with both the triquetrum and pisiform, and the triquetrum facet on the hamate is relatively proximodistally oriented in dorsal view. The Nacholapithecus capitate possesses a moderate distopalmar hook‐like process and separated radial articular facets for the trapezoid and the second metacarpal due to the carpometacarpal ligament attachment that is absent in the Proconsul capitate. Discussion: The carpal anatomy of Nacholapithecus is similar to that of the early Miocene hominoid Proconsul . However, Nacholapithecus wrist anatomy appears to exhibit slightly more emphasized stability. Am J Phys Anthropol 160:469–482, 2016. © 2016 Wiley Periodicals, Inc.